Alcohol dependence activates ventral tegmental area projections to central amygdala in male mice and rats. (16th December 2020) - Avegno, Elizabeth M.; Kasten, Chelsea R.; Snyder, William B.; Kelley, Leslie K.; Lobell, Thomas D.; Templeton, Taylor J.; Constans, Michael; Wills, Tiffany A.; Middleton, Jason W.; Gilpin, Nicholas W.
Abstract: The neural adaptations that occur during the transition to alcohol dependence are not entirely understood but may include a gradual recruitment of brain stress circuitry by mesolimbic reward circuitry that is activated during early stages of alcohol use. Here, we focused on dopaminergic and nondopaminergic projections from the ventral tegmental area (VTA), important for mediating acute alcohol reinforcement, to the central nucleus of the amygdala (CeA), important for alcohol dependence‐related negative affect and escalated alcohol drinking. The VTA projects directly to the CeA, but the functional relevance of this circuit is not fully established. Therefore, we combined retrograde and anterograde tracing, anatomical, and electrophysiological experiments in mice and rats to demonstrate that the CeA receives input from both dopaminergic and nondopaminergic projection neurons primarily from the lateral VTA. We then used slice electrophysiology and fos immunohistochemistry to test the effects of alcohol dependence on activity and activation profiles of CeA‐projecting neurons in the VTA. Our data indicate that alcohol dependence activates midbrain projections to the central amygdala, suggesting that VTA projections may trigger plasticity in the CeA during the transition to alcohol dependence and that this circuit may be involved in mediating behavioral dysregulation associated with alcohol dependence. Abstract : The VTA is engaged early in alcohol use, and VTA projections to CeA may contribute to CeA plasticity after chronic alcohol exposure. We provide anatomical and molecular characterization of the VTA‐CeA circuit in mice and rats and demonstrate activation of this circuit during withdrawal from chronic alcohol. Our results highlight the importance of understanding the crosstalk between brain reward and stress systems in addiction, and this line of research may inform development of treatment strategies for individuals living with AUD.